PENGARUH PARTISIPASI PENGANGGARAN, PENEKANAN ANGGARAN, KAPASITAS INDIVIDU, DAN KEJELASAN SASARAN ANGGARAN PADA SENJANGAN ANGGARAN - Erina, Ni Putu Dewik; Suartana, Wayan (E-Jurnal Akuntansi, 2016)
Normal 0 false false false EN-US X-NONE X-NONE This study aims to determine the effect of participation budgeting, budget emphasis, individual capacity, and budget goal clarity on budgetary slack. This research was conducted at the regional work units Gianyar regency. The population in this study is the structural SKPD Gianyar regency officials that its population is 151 respondents. The sample in this study using a non-probability sampling with purposive sampling. The number of samples in this research was 128 respondents. The analysis technique used multiple linear regression. These results indicate that the participation budgeting positive influence on budgetary slack, budget emphasis positive influence on budgetary slack, individual capacity slack negative effect on the budget, and budget goal clarity negative influence on budgetary slack. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";}
Keywords: Budget; Individual Capacity; Budgetary Slack